The problem of human dignity in its theological connotations under the conditions of the war of the russia against Ukraine - Ганна Кулагіна-Стадніченко (Cхід)
The author draws attention to the problem of human dignity as the basis of civilizational coexistence of subjects of different religious and secular beliefs. It is shown that neither international legal documents nor theological concepts provide a clear definition of the term “dignity”. Different readings refer to the meaningful, structural, dynamic meaning of this term. Based on the religious principles of tolerance, non-involvement and objectivity, this article examines human dignity in its theological connotations in view of the challenges of modern Ukrainian realities. The current positions of religious organizations, which traditionally enjoy the considerable trust of Ukrainian society, are articulated. Based on the generalization of the theoretical material and the statements of religious leaders of various denominations, the author concludes that in the conditions of the impossibility of political dialogue in the context of reconciliation with the aggressor, the idea of interreligious dialogue also needs urgent reconstruction, in particular, in particular, a direct answer to the question of whether dialogue can be the mission of the Church, conducted by it at the cost of truth and, at the same time, indulging human dignity, is needed.